Intratesticular Varicocele - Birkan, Zulfu; Kalayci, Tugce Ozlem; Karakeci, Ahmet; Sonmezgoz, Fitnet; Firdolas, Fatih (Derman Medical Publ, 2014)
Intratesticular varicocele is a rare condition seen in less than 2% of the symptomatic men, undergoing testicular sonography. We report a case of 28-years-old patient who presented with scrotal pain and diagnosed as unilateral intratesticular varicocele with scrotal color Doppler ultrasonography. It was associated with extratesticular varicocele. Intratesticular varicocele has a variable sonographic appearence. Color Doppler sonography is important in confirming the diagnosis and the management of varicocele.
Keywords: Intratesticular Varicocele; Color Doppler Sonography; Scrotum